2018
DOI: 10.1016/j.athoracsur.2017.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Does Donor Age and Double Versus Single Lung Transplant Affect Survival of Young Recipients?

Abstract: Reasonable posttransplant outcomes can be achieved with use of advanced age donors in all recipient groups. Double lung transplantation should be performed when older donors (age more than 60) are used in young recipients (age 50 or less).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In fact, several studies have shown that lungs from older donors can be used safely for transplantation. [222324] Another common reason for exclusion of donors for lung transplantation with the ideal criteria is an abnormal chest radiograph. Up to 41%–61% of lung donors can have abnormal chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have shown that lungs from older donors can be used safely for transplantation. [222324] Another common reason for exclusion of donors for lung transplantation with the ideal criteria is an abnormal chest radiograph. Up to 41%–61% of lung donors can have abnormal chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…29 A further study by Whited and colleagues demonstrated similar findings, in that reasonable transplant outcomes were achieved across all recipient age groups with the use of donors aged over 60 years. 30…”
Section: Candidate Listingmentioning
confidence: 99%
“…The PCC group received a median dose of 703 units pre-CPB and 1405 units post-CPB, for a median total dose of 2108 units. [5][6][7][8][9][10]; P < .001), and packed red cells (5 [3][4][5][6][7] vs 2 [1.25-2.75]; P < .001) and had a shorter time to chest closure (619 vs 548 minutes; P = .008). There were no differences in platelet transfusion, ICU stay or hospital LOS, acute kidney injury (AKI), or mortality.…”
Section: Prothrombin Complex Concentrate (Pcc)mentioning
confidence: 99%
“…Costa et al 21 Villavicencio et al 23 Barbero et al 24 Inci et al 25 DCD results in transplantable organs at a rate near that of DBD; 24-hour PGD is worse in DCD but resolves by 72 hours Survival outcomes identical to DBD Survival rates are comparable Survival trended worse in DCD Survival trended better in DCD Procurement: donor age Whited et al 4 Older grafts had worse survival outcomes in single lung transplant with young recipients Procurement: TBI Crawford et al 19 No difference in survival Procurement: IVDU Whited et al 18 IVDU donors more common; no difference in survival for recipients Procurement: naloxone Dhar et al 30 No protection from development of hypoxia in grafts treated with naloxone vs saline Procurement: volatile vapor…”
Section: Procurement: Dcdmentioning
confidence: 99%